Analysis of unsteady flow and fluid exciting forces of multistage centrifugal pump based on actual size. (February 2022) - Cui, Baoling; Zhang, Yingbin; Huang, Yakun; Zhu, Zuchao
The unsteady flow and fluid exciting force inside the multistage centrifugal pump were analyzed on the basis of large eddy simulation (LES). The reliability of the numerical simulation was verified by the experimental performance. The performance of pump calculated was closer to the experimental one than that by the Reynolds time average turbulence model, and the errors were 0.36% and 1.14% at the design flow rate, respectively. The results showed that the different distribution and magnitude of the inlet velocity at each stage impeller contributed to the difference of the head for each one. With the increase of flow rates from 0.4Q to 1.2Q, the rule of axial forces for each stage was roughly the same but the total axial force increased from 25.02kN to 29.92kN. The radial force in the Z direction was smaller than the one in the Y direction, and the amplitude of the main frequency in the Z direction changed more gently for the double tongue. Adopting back-to-back impeller distributions can effectively reduce the axial force. The symmetric distributed double tongue can reduce the radial force and play a key role in reducing the vibration of the centrifugal pump.